Evaluating basic knee arthroscopy skills in orthopaedic trainees in a limited resourse setting - Berry, Kirsty (Division of Orthopaedic Surgery, 2024)
Background: Orthopaedic training in Southern Africa is largely focused on trauma, although elective procedures, such as knee arthroscopy are increasing. This is especially true in the private sector where most trainees will practice. The primary aim of this study was to assess the arthroscopic competency of orthopaedic trainees in a setting of limited resources. Methods: A prospective observational cohort study was carried out. Orthopaedic trainees of a Southern African university hospital performed basic arthroscopy on a knee model. Their surgical competency was assessed by two surgeons proficient in arthroscopy using the modified Basic Knee Arthroscopy Skill Scoring System (mBAKSSS). Results: A total of 16 trainees (12 male) were included (6 junior and 10 senior trainees). The median age of participants was 36 (34.8, 37). The median mBAKSSS was 28.0 (20.3, 32.5) but showed a large variability (12.0-42.5). The overall reliability was excellent with Cronbach's Alpha of 0.91 and interclass correlation of 0.91 [95% CI 0.75, 0.97]. Conclusions: The average knee arthroscopy proficiency of our trainees is comparable to those of international training programs, but there was great variability with inconsistent skills amongst the trainees. This calls for improved and reproducible arthroscopy training and skills transfer, exposure to procedures and ongoing assessment. Level of Evidence: II (Prospective observational cohort study)